2016
DOI: 10.1007/s00586-016-4396-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study using anterior approach did not show association between Modic 1 changes and low grade infection in lumbar spine

Abstract: Unlike the posterior approach where contamination is common, the anterior video-assisted approach allows a biopsy without skin contact. This approach to the spine is the most effective way to eliminate the risk of contamination. Our results confirm the absence of any relationship between infection and disc degeneration. We suggest that the 6 positive samples in our study may be related to contamination. The absence of infection at 1-year followup is an additional argument in favour of our results. In conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 34 publications
1
58
0
Order By: Relevance
“…On the other hand, several of the previous studies reported a low prevalence of culture-positivity in resected lumbar discs [5, 6, 10]. In this light, even if P .…”
Section: Introductionmentioning
confidence: 86%
“…On the other hand, several of the previous studies reported a low prevalence of culture-positivity in resected lumbar discs [5, 6, 10]. In this light, even if P .…”
Section: Introductionmentioning
confidence: 86%
“…One rationale is that the P. acnes isolated in these cases may have been contamination rather than original growth because P. acnes is commensal flora existing on skin and it may readily contaminate the intervertebral discs during tissue harvesting [13, 14]. Another point was that some studies did not find any bacteria at all [1517]. For example, one study covering more than 300 samples found no original growth of P. acnes in any intervertebral discs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Another point was that some studies did not find any bacteria at all [1517]. For example, one study covering more than 300 samples found no original growth of P. acnes in any intervertebral discs [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Rigal et al. studied 313 patients with degenerative disc disease (not herniation) and found bacteria in less than 2% with no association to Modic changes. Carricajo examined 54 patients with LDH and found the rate of positive cultures to be similar between disc samples and control samples from sourrounding muscle and ligament.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Propionibacterium acnes is typically classified as a ubiquitous, non-pathogenic, commensal microorganism and the apparent colonization of disc tissue by P. acnes has been interpreted to be a result of contamination due to contradictory rapports. Rigal et al (6) studied 313 patients with degenerative disc disease (not herniation) and found bacteria in less than 2% with no association to Modic changes. Carricajo (7) examined 54 patients with LDH and found the rate of positive cultures to be similar between disc samples and control samples from sourrounding muscle and ligament.…”
mentioning
confidence: 99%